Mesenchymal Stromal Cell Secretome for the Treatment of Immune-Mediated Inflammatory Diseases: Latest Trends in Isolation, Content Optimization and Delivery Avenues - Elena Munoz-Perez; Ainhoa Gonzalez-Pujana; Manoli Igartua; Edorta Santos-Vizcaino; Rosa Maria Hernandez (MDPI AG, 2021)
Considering the high prevalence and the complex pharmacological management of immune-mediated inflammatory diseases (IMIDs), the search for new therapeutic approaches for their treatment is vital. Although the immunomodulatory and anti-inflammatory effects of mesenchymal stromal cells (MSCs) have been extensively studied as a potential therapy in this field, direct MSC implantation presents some limitations that could slow down the clinical translation. Since the beneficial effects of MSCs have been mainly attributed to their ability to secrete a plethora of bioactive factors, their secretome has been proposed as a new and promising pathway for the treatment of IMIDs. Formed from soluble factors and extracellular vesicles (EVs), the MSC-derived secretome has been proven to elicit immunomodulatory effects that control the inflammatory processes that occur in IMIDs. This article aims to review the available knowledge on the MSC secretome, evaluating the advances in this field in terms of its composition, production and application, as well as analyzing the pending challenges in the field. Moreover, the latest research involving secretome administration in IMIDs is discussed to provide an updated state-of-the-art for this field. Finally, novel secretome delivery alternatives are reviewed, paying special attention to hydrogel encapsulation as one of the most convenient and promising strategies.